Jovens rurais de São Carlos - SP: circulação cotidiana, projetos de vida e os sentidos da escola - Farias, Magno Nunes (2021)
This thesis aims to understand the aspects that involve the condition of rural youth life, as well as the everyday circulation, life projects and meanings of the school, taking the case of the rural youth of the city of São Carlos/SP. It was intended to understand and analyze what are the macro and microsocial aspects that involve the condition of youth life, limiting and/or enhancing the respective living. Thus, the objective was to determine how the everyday circulation of these young people is constituted, considering the traffic in the territories and communities; their life projects; and, finally, the meanings attributed to the school and how it marks such life projects and everyday circulation. With this study, we aimed to contribute to a critical analysis of the phenomena that pervade this population, in favor of solving problems that restrict their participation and social insertion. In addition, it was also thought to encourage advances in research enrolled in the field of rural youth and education, responding to a shortage of productions on the subject. For this purpose, the investigation was based mainly on theoretical and methodological excerpts from a Marxist basis. It is a research that dialogues with assumptions of participatory research and social occupational therapy, considering that it was based on a study carried out by an occupational therapist researcher. For the collection/production of data, “Workshops of dynamics, activities and projects”, “Individual and Territorial Follow-up” (through interviews, informal conversations, joint circulation and activities) and Questionnaire, directed to the production of oral narratives, written, imagery or audiovisual, which were later analyzed in their content. According to the data, these are poor young people, members of class-who-live-from-work. These people like to live in the rural territory, above all, for the tranquility of the space, however, the conditions that permeate the limitations of access to public and private services (health services, education, transport, leisure spaces for meetings, sociability and fun) mark the feeling of isolation in their experiences. In the context of everyday circulation, they point out that the central limits are the absence of transportation, the lack of money and, sometimes, barriers imposed by parents or guardians. Young people are able to find escape points to overcome these limitations, but within that the school still remains the central space that produces everyday circulation, in the coming and going, in the promotion of meetings, fun and sociability, although little dialogue with those indicated needs, which creates conflicts. In relation to life projects, young people build projects that have as main focus the insertion in the labor market and higher education, which are generally associated. Projects are often more tied to the most urgent needs (thus called projects-necessity), such as getting a job to help parents financially, paying for college or courses and having greater autonomy in local territory, especially for young people most affected by poverty. Other projects are aimed at more distant futures, linked to dreams (the projects-dreams), such as being more socially recognized professionals, getting to know other countries and cultures and more, which go beyond the locality. Thus, it is identified that many life projects refer to projects for wider circulation, comprising beyond the local community, which often demands actions that the rural territory does not offer, since the intent is incompatible with staying in that territory. Finally, there is an urgent need for public policies for rural youths based on the emancipatory everyday circulation, in which the school, especially in the context of high school, has the potential to become a center of creativity, which in articulation with other equipment in the rural territory, can expand the experience of life and the chances of coming and going freely - producing the being more of these young people.